Eco-friendly Edible Film from Chicken Bone Waste and Tapioca Starch - Sri Hilma Siregar; P. Prasetya; Aulia Rizki Ramadhanti; Rian Putra; Siti Zahidah (Jurnal Kimia Sains dan Aplikasi, 2022)
The manufacture of edible film from chicken bone gelatin incorporated with starch is essential for Indonesia, where most Muslims are. This is related to Shari’a law which requires Muslims to consume only halal food. Gelatin made from chicken bones is guaranteed to be halal. This study aimed to determine the process of extracting chicken bone waste with acid solvents, making the edible film, and the characterization of chicken bone edible film. This research started with extracting gelatin from chicken bone waste. The 5 g of extracted chicken bones were mixed with 40% w/v glycerol, starch (0, 5, 10, 15% w/v), and distilled water, then heated at 50°C. The mixture was printed in a petri dish (15 cm in diameter) and dried for 24 hours. The edible films were evaluated for physicochemical and mechanical properties, such as tensile strength, elongation, thickness, water resistance, WVTR, and degradation test. Edible film characterization used FTIR, SEM, XRD, and TGA. The optimum condition of the extraction procedure was obtained by using 5% HCl, which produces 8.22172% yield of gelatin with pH of 6.0, water content of 8%, and ash content of 0.945%. In the thickness test, the more significant the starch concentration added, the greater the thickness of the edible film produced. The edible film exhibited a decrease in tensile strength and an increase in elongation along with increasing starch concentration. The results of the WVTR test were only starch concentrations of 0 and 15% that meet the standards, while all concentrations in the water resistance did. The results of FTIR chicken bones with variations in starch and the addition of glycerol as a plasticizer have functional groups N-H, O-H, C-O, C=O, C-H, C-N. Edible films without the addition of starch were utterly degraded within 30 days.